Analisis Faktor-Faktor Pengambilan Keputusan Mahasiswa Memilih Program Studi Administrasi Bisnis pada Fakultas Ilmu Sosial dan Ilmu Politik UPN “Veteran” Jawa Timur - Rusdi Hidayat; Acep Samsudin; Firdausii Khoirunnisa; Alissa Azizah Herman Susilo; Rangga Eka Saputra; Daivan Putra Tanzaga; Ely Nanda Khamdiyah (Transformasi Manageria: Journal of Islamic Education Management, 2023)
Education is an essential part of a human being's life, therefore decision-making in matters of education is something that really needs attention. One of them is making the decision to take the study program to be pursued in Higher Education, the many choices that can be made make prospective students need to make the right decision in deciding which study program to pursue. The research method used was a qualitative method with a questionnaire as a data collection technique, while the research participants came from business administration study program students from the East Java "Veteran" National Development University as many as 31 students (9 boys and 22 girls) aged between 18 to 20 years . The results of this study indicate that students choose the business administration study program because of their interests, job prospects, aspirations, educational background, parents, and easy admission opportunities. Keywords: Student, business administration, East Java Veterans National Development University, decision making.